(3JMUjd GdoeQGe ef JGQjN GdHdO GdMQGes - (3eMeO Hf CMeO Hf Ydj, Jbj GdOjf, CHh GdWjH Gdecj GdMSfj,J (B832 (3g` s ((3eMeO Hf eMeO Hf eMeO GdefTGhj s)
(3ChdgG (B:s
(3GdMQeI hCcKQajgG GdHQcI hGdQMeI s
(3BNQgG (B:s
(3Ke cedJg ai ChGFd SfI JSY YTQI hKeGfeGFI HecI GdeTQaI hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
Keywords: (3GdJGQjNs